Research Article Introductions as Hero Narratives: A Reading Strategy for Undergraduate Students - Vroom, Jonathan (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
This article describes a strategy for teaching undergraduate students to read research articles (RAs)—called the hero narrative reading strategy. This strategy modifies an existing approach to reading RAs (the Scientific Argumentation Model [SAM]), which teaches students to identify an article’s rhetorical moves. The hero narrative reading strategy relabels the rhetorical moves that the SAM identifies in RA introductions (Motive and Objective), and it frames RA introductions as hero narratives; students are taught to see RA writers as making hero claims—claims that they are stepping up to address a critical problem that previous research has not adequately addressed. This strategy can help students to understand the rhetorical structure of RAs.